PENERAPAN METODE BERMAIN PERAN UNTUK MENINGKATKAN PRESTASI BELAJAR IPS SISWA KELAS V DI MI BUSTANUL ULUM KOTA BATU - Achmad Muzayyin Abdillah (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
This study was to observe the application of the role playing method to improve social studies achievement of fifth grade students at MI Bustanul Ulum Batu City in February 2020. The researcher used a descriptive qualitative method. The class observed in this study was fifth grade students. Observations were made for 3 days to see the condition of the class during social studies and student learning outcomes after using the role playing method and before using the role playing method. this can be proven by the application of the role playing method which is still very minimal used by the teacher. The lack of application of the role playing method is caused by the lack of creative teacher in developing the application of the method sometimes so that it can be concluded based on the results of the study that the application of the role playing method is very influential on the learning outcomes of fifth grade students at MI Bustanul Ulum Batu City in February 2020.